a-minimal sets and related topics in transformation semigroups (II) - Masoud Sabbaghan; Fatemah Ayatollah Zadeh Shirazi (International Journal of Mathematics and Mathematical Sciences)
We give some generalizations of proximal relation and distal structure relation of a transformation semigroup in terms of A-minimal¯ sets and A-minimal¯¯ sets instead of minimal right ideals and conclude similar results.